Consumer Behavior dalam Memilih Produk Kosmetik Halal (Studi Masyarakat Desa Drajat, Desa Banjarwati dan Dusun Banjaranyar) - Kolifatus Sania; Nashihin; Musbikhin (Al-Muzdahir : Jurnal Ekonomi Syariah, 2020)
Consumer Behavior or consumer behavior is an action taken by consumers to achieve and fulfill their needs both to use, consume and spend goods and services. In the people of Drajat Village, Banjarwati Village, and Banjaranyar Hamlet, research will be carried out on the Consumer Behavior of the community in choosing halal cosmetic products. This study aims to determine how consumer behavior in choosing halal cosmetic products in the people of Drajat Village, Banjarwati Village, and Banjaranyar Hamlet. The approach in this research is quantitative research. The population in this study is the people of Drajat Village, Banjarwati, and Banjaranyar Hamlet with 100 samples of people taken by probability sampling technique. The independent variable in this study is Consumer Behavior (X) while the dependent variable is the decision to choose halal products (Y). Data collection techniques in this study were questionnaires and observation. Test the instrument using the validity test and the reliability test. The data analysis technique used simple linear regression analysis. Based on the results of the study, the test on cultural factors obtained a significance value of Tcount smaller than Ttable (0.457>0.192), the test results on social factors obtained a significance value of Tcount smaller than Ttable (0.356>0.192), the test results on personal factors obtained a significance value of Tcount greater than Ttable (0.591>0.192), the test results on psychological factors obtained a significance value of Tcount less than Ttable (0.506>0.192). From this explanation, it can be concluded that the personal factor with the indicator code PRB 2 (has the greatest significance value on Consumer Behavior in choosing halal cosmetic products in Drajat Village, Banjaranyar, and Banjarwati Hamlet, namely (0.591> 0.192), then H0 is rejected and Ha is accepted. Meanwhile, other factors have a smaller significance value than personal factors.